2016
DOI: 10.7314/apjcp.2015.16.18.8287
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate Synthase Polymorphisms and Risk of Lung Cancer among the Jordanian Population: a Case Control Study

Abstract: Background: Thymidylate synthase (TS) catalyzes the methylation of deoxyuridylate to deoxythymidylate and is involved in DNA methylation, synthesis and repair. Two common polymorphisms have been reported, tandem repeats in the promoter-enhancer region (TSER), and 6bp ins/del in the 5'UTR, that are implicated in a number of human diseases, including cancer. The association between the two polymorphisms in risk for lung cancer (LC) was here investigated in the Jordanian population. Materials and Methods: An age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Shen et al [40] found that the del6/del6 genotype of TS 3′-UTR was associated with significantly increased gastric cancer risk, Sumen et al [41] suggested that 3R allele, 2R/3R and 3R/3R genotypes were risk factors for gastric cancer, whereas Araújo et al [55] did not obtain a significant relationship between TS 5′-UTR 2R/3R and 3′-UTR del6/ins6 polymorphisms and gastric cancer susceptibility. Studies have also shown that TS polymorphisms might be associated with other cancers’ risks such as colon cancer [56], lung cancer [57] and oral squamous cell carcinoma [58]. In addition, genetic variation in TS gene may affect carcinogenesis through the regulation of gene expression, the status of the dNTP pool and drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al [40] found that the del6/del6 genotype of TS 3′-UTR was associated with significantly increased gastric cancer risk, Sumen et al [41] suggested that 3R allele, 2R/3R and 3R/3R genotypes were risk factors for gastric cancer, whereas Araújo et al [55] did not obtain a significant relationship between TS 5′-UTR 2R/3R and 3′-UTR del6/ins6 polymorphisms and gastric cancer susceptibility. Studies have also shown that TS polymorphisms might be associated with other cancers’ risks such as colon cancer [56], lung cancer [57] and oral squamous cell carcinoma [58]. In addition, genetic variation in TS gene may affect carcinogenesis through the regulation of gene expression, the status of the dNTP pool and drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%